Radiofrequency Ablation in Primary Aldosteronism - Lee, Yun-Ni; Drake, William Martyn (Experimental and Clinical Endocrinology & Diabetes, 2023)
The radiofrequency ablation (RFA) technique has been extensively used in the treatment of primary malignancies and metastases and has been recently deployed for the treatment of unilateral primary aldosteronism (PA) as an alternative to whole unilateral adrenalectomy.Current evidence comparing RFA with unilateral adrenalectomy in the treatment of PA so far has been variable, with studies being retrospective and small-scale, but it remains a very attractive option as a potentially less invasive treatment option compared to adrenalectomy.This review article describes the procedure, and provides evidence and the possible future direction of RFA in the treatment of unilateral PA.
Keywords: Hypertension<Cardiovascular incidences; Coronary syndrome<Cardiovascular incidences; Cardiovascular risk management<Cardiovascular incidences